miR825-5p targets the TIR-NBS-LRR gene MIST1 and down-regulates basal immunity against Pseudomonas syringae in Arabidopsis - López-Márquez, Diego; Del Espino Pérez, Ángel; López-Pagán, Nieves; Rodrígez-Negrete, Edgar A.; Rubio-Somoza, Ignacio; Ruiz-Albert, Francisco Javier; Rodríguez-Bejarano, Eduardo; Beuzón-López, Carmen del Rosario (Oxford University Press, 2021)
Plants encode numerous intracellular receptors known as nucleotide-binding leucine-rich repeat receptors (NLRs) that recognize pathogen-derived effectors or their activity to activate defenses. miRNAs regulate NLR genes in many species, often triggering the production of phased siRNAs (phasiRNAs). Most such examples involve genes encoding NLRs carrying coiled-coil domains, although a few include genes encoding NLRs carrying a Toll/interleukin-1 domain (TNL). Here, we characterize the role of miR825-5p in Arabidopsis, using a combination of bioinformatics, transgenic plants with altered miRNA levels and/or reporters, small RNAs, and virulence assays. We demonstrate that miR825-5p down-regulates the TNL MIST1 by targeting for endonucleolytic cleavage the sequence coding for TIR2, a highly conserved amino acid motif, linked to a catalytic residue essential for immune function. miR825-5p acts as a negative regulator of basal resistance against Pseudomonas syringae. miR825-5p triggers the production from MIST1 of a large number of phasiRNAs that can mediate cleavage of both MIST1 and additional TNL gene transcripts, potentially acting as a regulatory hub. miR825-5p is expressed in unchallenged leaves and transcriptionally downregulated in response to pathogen-associated molecular patterns (PAMPs). Our results show that miR825-5p, which is required for full expression of PAMP-triggered immunity, establishes a link between PAMP perception and expression of uncharacterized TNL genes.
Keywords: Receptores celulares; Arabidopsis; Gene silencing; miRNA; phasiRNAs; Plant immunity; Pseudomonas syringae; PTI; Resistance genes